Pengaruh Aset Pajak Tangguhan, Beban Pajak Tangguhan, dan Perencanaan Pajak Terhadap Manajemen Laba - Nurul Hikmah; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Job appraisal can be seen from achieving profit through a company. The importance of earnings management causes the need for in-depth studies of the factors that affect earnings management. This study has the purpose of determine the effect of deferred tax assets, deferred tax expence, and tax planning on earnings management. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange during 2015-2017. Sample selection was done by purposive sampling method. The sample used in this study were 30 manufacturing companies on the Indonesia Stock Exchange during 2015-2017 doing report and conducting financial publications statements in Rupiah, audited by auditor. The data analysis technique used is descriptive. Hypothesis test with partial t test is known that deferred tax expense have a significant effect on earnings management. However, tax planning has no effect on earnings management.